C‐Myc‐induced circ‐NOTCH1 promotes aggressive phenotypes of nasopharyngeal carcinoma cells by regulating the miR‐34c‐5p/c‐Myc axis. (6th April 2021) - Huang, Wei; Song, Wei; Jiang, Yunfei; Chen, Lejun; Lu, Hong
Abstract: Nasopharyngeal carcinoma (NPC) is the subclass of head and neck cancer with the highest incidence among otolaryngology malignancies. A growing amount of evidence has proven that circular RNAs (circRNAs) play key roles in the progression of multiple cancers. It has been reported that circ‐NOTCH1 is a novel circRNA and functions as an oncogene in gastric cancer, while the regulatory mechanism of circ‐NOTCH1 in NPC remains unknown. In the present research, our findings revealed that circ‐NOTCH1 was overexpressed in NPC tissues and cells. Circ‐NOTCH1 knockdown suppressed NPC cell proliferation, invasion, and migration. Subsequently, we discovered that c‐Myc can activate circ‐NOTCH1 by binding to the NOTCH1 promoter. c‐Myc functioned as a tumor promoter in NPC cells. Mechanistically, circ‐NOTCH1 served as a competitive endogenous RNA to modulate c‐Myc expression by sponging miR‐34c‐5p. Additionally, overexpression of c‐Myc reversed the circ‐NOTCH1 knockdown‐mediated inhibition of NPC cellular progression. Overall, this study suggested that c‐Myc‐induced circ‐NOTCH1 promoted malignant phenotypes of NPC cells by regulating the miR‐34c‐5p/c‐Myc axis.